Analysis of Flight Operation Officer’s Understanding of Navblue Flight Plan in Operations at PT Wings Abadi Airlines - Mairah Novita; Sri Sutarwati; Setyamartana Parman (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
Wings Air, as a regional carrier, faces operational challenges such as short runways, high-altitude airports, and limited navigation facilities. Under these conditions, Flight Operation Officers (FOO) are responsible for preparing flight plans using the Navblue Flight Plan system, which has been implemented since 2023. However, several Operational Flight Plans were found to be inconsistent with standard operating procedures (SOP). The errors include incorrect fuel calculations, misinterpretation of weather data, suboptimal route selection, and inaccurate aircraft performance data input. These issues may result in flight delays, fuel inefficiency, and potential safety risks. This study aims to analyze the level of FOO understanding of the system. It also examines the operational impact of system misuse. A mixed-method approach combining quantitative and qualitative methods was employed. Data were collected through questionnaires distributed to 15 FOOs, in-depth interviews with three key informants, observations, and documentation. The results indicate that the FOO understanding level reached 88%, categorized as very good. FOOs are generally able to perform procedures in accordance with SOP. Nevertheless, challenges remain in database integration and human error during data entry. Overall, FOOs demonstrate comprehensive understanding, but improvements in system integration and operational accuracy are still required.